Ultrasound versus computed tomography guided percutaneous needle biopsy for subpleural pulmonary lesions - Zhou, Yaoyao; Wang, Xuhong; Han, Rui; Zhang, Shengmin (Frontiers in Oncology, 2024)
BackgroundSub-pleural pulmonary lesions (SPLs) can be diagnosed by percutaneous needle biopsy (PNB) guided by both computed tomography (CT) and ultrasound (US). This investigation aims to compare the diagnostic accuracy and safety between US- and CT-guided PNB for SPLs.MethodsThis retrospective study analyzed SPL patients who underwent CT- or US-guided PNB in our hospital between January 2022 to January 2023. Furthermore, the technical success rates, duration of procedure, diagnostic yield, diagnostic accuracy, pneumothorax rates, and hemoptysis rates were compared between the 2 groups. Pneumothorax risk factors were assessed via the univariate and multivariate logistic regression tests.ResultsThe data indicated that 213 patients who underwent CT- (n = 108) or US-guided (n = 105) PNB diagnosis had SPLs at the final diagnosis. Furthermore, both groups indicated similar operation times (20.1 ± 8.1 min vs. 19.9 ± 6.9 min, p = 0.793). The diagnostic accuracy and yield of the US group were 100% and 64.8%, respectively, whereas those of the CT group were 99.1% and 72.2%, respectively. Moreover, no significant differences were observed in diagnostic accuracy (p = 1.000) and diagnostic yield (p = 0.561) between the 2 groups. The CT group indicated markedly higher rates of chest tube insertion (6.5% vs. 0.0%, p = 0.014) and pneumothorax (24.1% vs. 1.9%, p = 0.001) than the US group. However, the hemoptysis rates were comparable between the 2 groups (2.7% vs. 2.9%, p = 1.000). In addition, CT guidance was the independent risk factor of pneumothorax (p = 0.003).ConclusionsIn summary, this research indicated that both US- and CT-guided PNB have high diagnostic accuracy for SPLs. However, US guidance may provide better safety than CT guidance.